1981
DOI: 10.1007/bf00384258
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of enhanced UV-B irradiation on the growth and composition of plants

Abstract: Barley (Hordeum vulgare), corn (Zea mays), bean (Phaseolus vulgaris), and radish (Raphanus sativus) seedlings were continuously irradiated under a lighting device for 5-10 d at an increased ultraviolet (UV)-B fluence rate. In their growth parameters, composition, and leaf surface, these four species responded differently to the increased UV-B exposure. Bean seedlings suffered the most serious effects, radish and barley less, and corn was hardly influenced at all. In all plant species, the fresh weight, the lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
85
3

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(94 citation statements)
references
References 22 publications
6
85
3
Order By: Relevance
“…Chl b is more affected by UV-B radiation than Chl a, which results in an increase of the ratio Chl a/b. These observations are in agreement with previously reported data about the effect of UV-B on pigments [ 7,9 ], indicating a preferential destruction of Chl b biosynthesis and/or degradation of precursors upon UV-B exposure. Comparison between the control and EBR-treated plants, subjected to UV-B irradiation, indicates that exogenous application of EBR has a protective effect against UV-B-induced pigment destruction, Chl b being more protected by EBR than Chl a, thus leading to a decrease of Chl a/b ratio (Table 1).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Chl b is more affected by UV-B radiation than Chl a, which results in an increase of the ratio Chl a/b. These observations are in agreement with previously reported data about the effect of UV-B on pigments [ 7,9 ], indicating a preferential destruction of Chl b biosynthesis and/or degradation of precursors upon UV-B exposure. Comparison between the control and EBR-treated plants, subjected to UV-B irradiation, indicates that exogenous application of EBR has a protective effect against UV-B-induced pigment destruction, Chl b being more protected by EBR than Chl a, thus leading to a decrease of Chl a/b ratio (Table 1).…”
supporting
confidence: 93%
“…The content of chlorophylls, carotenoids and UV-B absorbing compounds is frequently used as indicator of plant sensitivity to UV-B radiation ([ 8 ] and refs therein). It has also been demonstrated that the UV-induced effects on photosynthesis and pigment content depend on the radiation doses and duration of treatment [ 8,9 ].…”
mentioning
confidence: 99%
“…General symptoms of increased u.v.-B exposure include reductions in plant height (Sullivan & Teramura, 1988 ;Barnes, Flint & Caldwell, 1990) and biomass production (Tevini, Iwanzik & Thoma, 1981 ;Naidu et al 1993). There is large variation in plant response to u.v.-B between and within species.…”
Section: mentioning
confidence: 99%
“…One-third to one-half of all plant species tested are deleteriously affected by UV-B levels "above ambient" (Sullivan, 1992). A substantial number of studies have been conducted that have evaluated the potential consequences of an increase in UV-B radiation on many plants (Tevini et al, 1981;Teramura et al, 1990;Miller et al, 1994;Caldwell et al, 1998;Correia et al, 1998Correia et al, , 1999Li et al, 2000, Searles et al, 2001), but we have a rather limited understanding of the role that UV-B radiation plays in controlling cotton growth, development, yield and quality. Searles et al (2001) searched for "all suitable published studies" with field-based measurements of UV-B influences on vascular plants and found no studies on cotton.…”
Section: Introductionmentioning
confidence: 99%